A Review on Nanocarrier Mediated Treatment and Management of Triple Negative Breast Cancer: A Saudi Arabian Scenario - Nahvi, Insha; Belkahla, Sana; Biswas, Supratim; Chakraborty, Suparna (Frontiers in Oncology, 2022)
People have continued to be petrified by the devastating effects of cancer for decades and thus a pursuit for developing anticancer agents have seen an ever-increasing trend in the past few decades. Globally, breast cancer is the most common malignancy in women and the second most common cause of cancer-related deaths. In Saudi Arabia, breast cancer is the most common type of cancer among women, constituting almost 14.2% of the total cancer burden. Triple-negative breast cancer (TNBC) is a subtype of breast cancer, which is a pathologically diverse disease of higher grade characterized by the absence of the estrogen receptor (ER), the progesterone receptor (PR), and the human epidermal growth factor receptor 2 (HER2) expressions. Despite the considerable advancements achieved in the therapeutic management of cancer, TNBC remains an unbeatable challenge, which requires immediate attention as it lacks conventional targets for treatment, leading to a poor clinical prognosis. The present research goals are directed toward the development and implementation of treatment regimens with enhanced bioavailability, targetability, minimized systemic toxicity, and improved outcomes of treatment options. The present treatment and management scenario of TNBC continues to provoke oncologists as well as nanomedical scientists to develop novel and efficient nanotherapies. Lately, scientific endeavors have addressed the importance of enhanced availability and targeted cellular uptake with minimal toxicity, which are achieved by the application of nano drug-carriers. This review intends to summarize the incidence rates of TNBC patients, the importance of nanotherapeutic options for patients suffering from TNBC, the identification of promising molecular targets, and challenges associated with the development of targeted nanotherapeutics with special reference to the Saudi Arabian context.